(untitled) (Journal of the College of Basic Education, 2023)
Practical education (application) is considered one of the basics of teacher preparation and education. It is necessary and indispensable.about it, and the basic essence in its meaning is that it is an organized opportunity in which students and teachers are givenPractice in the sense of work in classroom situations inside and outside the classroom (Jaberand Salam (1985: 77): Practical education is seen as the means for transferring experiences and skills of numbersTeachers in the college or institute to the community (Abu Jaber, Katami) (1998: 109).The educational heritage summarizes for us the benefits of scientific education, as educators agree that practical education givesThe number programs have a theoretical, practical nature, as without them these programs would have no meaning.During which the student teacher applies what he has learned of ideas, theories and information duringI studied it in practical application (Hamdan (1984: 18): through a survey view of the reality of education.The process in teacher preparation channels * In Iraq in terms of its supervision, he participates in the supervisionThe student teacher, each of the educational supervisor, the supervisor of specialization (scientific), and the director ofSchool and the distribution of degrees of practical education to those with different weights.Practical education aims to improve the performance of the student teacher through the teacher’s guidance and counseling.And assisting the supervisor in practical education, in addition to that, increasing his experience.It requires specialized supervisors who, if well chosen, can be counted as one of the important factors.In the success of practical education and the achievement of its objectives, there are elements that can help in achievingThe goals are the student, the teacher, the cooperating teacher, the school administration, and the interaction of these elements in a mannerpractical help in the success of practical education. Broadblet confirms that the testing processThe educational supervisor is one of the aspects that suffer from neglect in the practical education program. And whoAnother aspect, Lesile concluded that there is a fundamental problem in defining criteria for selecting